Download presentation

1
**9.5 - The Quadratic Formula**

2
**Quadratic Equation: x = -b ± √b2 – 4ac**

3
**Quadratic Equation: x = -b ± √b2 – 4ac**

for any quadratic equation in the form ax2 + bx + c = 0

4
**Ex. 1 a. Solve x2 + 4x + 2 = 0 using the. quadratic formula**

Ex. 1 a. Solve x2 + 4x + 2 = 0 using the quadratic formula. Round to the nearest hundredth.

5
**Ex. 1 a. Solve x2 + 4x + 2 = 0 using the. quadratic formula**

Ex. 1 a. Solve x2 + 4x + 2 = 0 using the quadratic formula. Round to the nearest hundredth. x2 + 4x + 2 = 0

6
**Ex. 1 a. Solve x2 + 4x + 2 = 0 using the. quadratic formula**

Ex. 1 a. Solve x2 + 4x + 2 = 0 using the quadratic formula. Round to the nearest hundredth. x2 + 4x + 2 = 0; a = 1

7
**Ex. 1 a. Solve x2 + 4x + 2 = 0 using the. quadratic formula**

Ex. 1 a. Solve x2 + 4x + 2 = 0 using the quadratic formula. Round to the nearest hundredth. x2 + 4x + 2 = 0; a = 1, b = 4,

8
**Ex. 1 a. Solve x2 + 4x + 2 = 0 using the. quadratic formula**

Ex. 1 a. Solve x2 + 4x + 2 = 0 using the quadratic formula. Round to the nearest hundredth. x2 + 4x + 2 = 0; a = 1, b = 4, c = 2

9
**Ex. 1 a. Solve x2 + 4x + 2 = 0 using the. quadratic formula**

Ex. 1 a. Solve x2 + 4x + 2 = 0 using the quadratic formula. Round to the nearest hundredth. x2 + 4x + 2 = 0; a = 1, b = 4, c = 2 x = -b ± √b2 – 4ac 2a

10
**Ex. 1 a. Solve x2 + 4x + 2 = 0 using the. quadratic formula**

Ex. 1 a. Solve x2 + 4x + 2 = 0 using the quadratic formula. Round to the nearest hundredth. x2 + 4x + 2 = 0; a = 1, b = 4, c = 2 x = -b ± √b2 – 4ac 2a x = -(4) ± √(4)2 – 4(1)(2) 2(1)

11
**Ex. 1 a. Solve x2 + 4x + 2 = 0 using the. quadratic formula**

Ex. 1 a. Solve x2 + 4x + 2 = 0 using the quadratic formula. Round to the nearest hundredth. x2 + 4x + 2 = 0; a = 1, b = 4, c = 2 x = -b ± √b2 – 4ac 2a x = -(4) ± √(4)2 – 4(1)(2) 2(1) x = -4 ± √16 – 8 2

12
**Ex. 1 a. Solve x2 + 4x + 2 = 0 using the. quadratic formula**

Ex. 1 a. Solve x2 + 4x + 2 = 0 using the quadratic formula. Round to the nearest hundredth. x2 + 4x + 2 = 0; a = 1, b = 4, c = 2 x = -b ± √b2 – 4ac 2a x = -(4) ± √(4)2 – 4(1)(2) 2(1) x = -4 ± √16 – 8 2 x = -4 ± √8

13
**Ex. 1 a. Solve x2 + 4x + 2 = 0 using the. quadratic formula**

Ex. 1 a. Solve x2 + 4x + 2 = 0 using the quadratic formula. Round to the nearest hundredth. x2 + 4x + 2 = 0; a = 1, b = 4, c = 2 x = -b ± √b2 – 4ac 2a x = -(4) ± √(4)2 – 4(1)(2) 2(1) x = -4 ± √16 – 8 2 x = -4 ± √8 x = -2 ± ½√8

14
**Ex. 1 a. Solve x2 + 4x + 2 = 0 using the. quadratic formula**

Ex. 1 a. Solve x2 + 4x + 2 = 0 using the quadratic formula. Round to the nearest hundredth. x2 + 4x + 2 = 0; a = 1, b = 4, c = 2 x = -b ± √b2 – 4ac 2a x = -(4) ± √(4)2 – 4(1)(2) 2(1) x = -4 ± √16 – 8 2 x = -4 ± √8 x = -2 ± ½√8 x = -2 + ½√8

15
**Ex. 1 a. Solve x2 + 4x + 2 = 0 using the. quadratic formula**

Ex. 1 a. Solve x2 + 4x + 2 = 0 using the quadratic formula. Round to the nearest hundredth. x2 + 4x + 2 = 0; a = 1, b = 4, c = 2 x = -b ± √b2 – 4ac 2a x = -(4) ± √(4)2 – 4(1)(2) 2(1) x = -4 ± √16 – 8 2 x = -4 ± √8 x = -2 ± ½√8 x = -2 + ½√8 x ≈ -0.59

16
**Ex. 1 a. Solve x2 + 4x + 2 = 0 using the. quadratic formula**

Ex. 1 a. Solve x2 + 4x + 2 = 0 using the quadratic formula. Round to the nearest hundredth. x2 + 4x + 2 = 0; a = 1, b = 4, c = 2 x = -b ± √b2 – 4ac 2a x = -(4) ± √(4)2 – 4(1)(2) 2(1) x = -4 ± √16 – 8 2 x = -4 ± √8 x = -2 ± ½√8 x = -2 + ½√8 x = -2 – ½√8 x ≈ -0.59

17
**Ex. 1 a. Solve x2 + 4x + 2 = 0 using the. quadratic formula**

Ex. 1 a. Solve x2 + 4x + 2 = 0 using the quadratic formula. Round to the nearest hundredth. x2 + 4x + 2 = 0; a = 1, b = 4, c = 2 x = -b ± √b2 – 4ac 2a x = -(4) ± √(4)2 – 4(1)(2) 2(1) x = -4 ± √16 – 8 2 x = -4 ± √8 x = -2 ± ½√8 x = -2 + ½√8 x = -2 – ½√8 x ≈ x ≈ -3.41

18
**b. Solve x2 – 5x + 3 = 0 using the. quadratic formula. Round to the**

b. Solve x2 – 5x + 3 = 0 using the quadratic formula. Round to the nearest hundredth.

19
**b. Solve x2 – 5x + 3 = 0 using the. quadratic formula**

b. Solve x2 – 5x + 3 = 0 using the quadratic formula. Round to the nearest hundredth. x2 – 5x + 3 = 0; a = 1, b = -5, c = 3 x = -b ± √b2 – 4ac 2a x = -(-5) ± √(-5)2 – 4(1)(3) 2(1) x = 5 ± √25 – 12 2 x = 5 ± √13 x = ½√13 x = ½√13 x ≈ x ≈ 0.70

Similar presentations

© 2021 SlidePlayer.com Inc.

All rights reserved.

To make this website work, we log user data and share it with processors. To use this website, you must agree to our Privacy Policy, including cookie policy.

Ads by Google